BAAL : informatie-orgaan Groep 7152. (Amsterdam : Groep 7152, 1972)
Fonds Suzan Daniel (FSD)
Periodiciteit : ? ; vanaf (1972) 7 : maandelijks
Redactie : Grote Kattenburgerstraat 82, Amsterdam
Nederlands
Periodiek